Christ as an Example in Poverning Ministry According to John 10. 11-15 towards Church Growth during the Covid 19 Pandemic - Enny Irawati (Budapest International Research and Critics University, 2021)
The purpose of the research that the author intends is to find how Christ is an example in the pastoral ministry according to John 10. 11-15, where the main essence of a shepherd in the text is the attitude possessed by the pastor, namely the willingness to give life for the sheep means the ability to sacrifice for the lives of the sheep or the congregation, by knowing well the life of the sheep and manifesting a loyal attitude towards the sheep. This writing is intended so that all of God's people understand well that about how a shepherd is intended to be able to understand his role as the main figure that ensures the continuity of the shepherding, namely how a shepherd has an attitude of responsibility, the right integrity in shepherding, and how a shepherd can shepherd by not pursuing wages, but shepherding by loving every sheep that herded. Some of the things that the author pays attention to in this research are how The pastor needs to be a character who must play the main role, as an example, who cares for the congregation, a person who is consistent in ministry, and some important attitudes, both by the pastor of the congregation, it can be noted that there is still a lack of understanding of the pastor's example of the growth of the church specifically based on John 10:11-15.